Hassan Abbas, Pakistan Nuclear Bomb: A story of Defiance, Deterrence, and Deviance - Mr. Samran Ali (CISS Insight Journal, 2018)
Pakistan’s nuclear program has received a lot of negative attention due to nuclear proliferation activities after the discovery of A.Q. Khan Network. Pakistan’s Nuclear Bomb is a book focusing on the proliferation activities of Abdul Qadeer Khan Network. Written by Hassan Abbas, a professor and chair of the Department of Regional and Analytical Studies at the National Defence University, Washington, DC this book is one of the several books and articles published in the West in the last few years on this topic. The title of the book is misleading. The title focuses on Pakistan’s nuclear weapons program, but the book discusses AQ Khan’s alleged proliferation links with Iran, North Korea, and Libya. In fact, AQ Khan was only supervising the Khan Research Laboratories while the Pakistan Atomic Energy Commission was overseeing all other nuclear activities. So far, Pakistan was following two parallel programs on its journey to nuclearization. The author addresses two main questions. Firstly; whether Khan alone was responsible for proliferation activities or he was carrying out these activities with the backing of the Pakistani state. Secondly, the book looks at the circumstances that led to the proliferation activities of the A.Q. Khan Network.